Sharing Privacy Information in Credit Analysis Environment - Brocardo M.L. (2015)
© 2015 IEEE.Credit analysis is used by financial companies to grant credit to customers. The analysis is expensive, bureaucratic, and requires the collection of customer personal information. However, shopping malls are selling goods in several installments and need a simple, fast, and cheap process to grant credit to their customers. One way to improve the efficiency of this process is to facilitate the sharing of private information from customers and stores. The challenge here is how to share private information without disclosing the identity of its owner. Here we propose a protocol to share information while preserving the privacy of the customer as well as the information of the commercial institution.